2012
DOI: 10.4111/kju.2012.53.8.569
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immediate Primary Repair and Delayed Urethroplasty in Men with Bulbous Urethral Disruption after Blunt Straddle Injury

Abstract: PurposeThe aim of this study was to analyze the outcomes of immediate primary repair (IPR) compared with delayed repair (DR) after initial suprapubic cystostomy.Materials and MethodsWe reviewed the records of 60 patients with bulbous urethral disruption after blunt trauma from February 2001 to March 2011. Seventeen patients who presented in an acute injury state underwent IPR; 43 patients underwent DR after the initial suprapubic cystostomy. None of the patients had undergone previous urethral manipulation. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Stricture formation after straddle injury is very high and thus all patients undergoing urinary diversion require follow-up surveillance using uroflowmetry, retrograde urethrogram and/or cystoscopy. 129 …”
Section: Guideline Statementsmentioning
confidence: 99%
“…Stricture formation after straddle injury is very high and thus all patients undergoing urinary diversion require follow-up surveillance using uroflowmetry, retrograde urethrogram and/or cystoscopy. 129 …”
Section: Guideline Statementsmentioning
confidence: 99%
“…We did not find any such study in Chinese literature, but there is a study from Korea that compared primary repair with delayed repair. That study reported that in AUI, primary repair had comparable result with delayed repair [25] .…”
Section: Discussionmentioning
confidence: 86%
“…Table 1 listed the results of 23 studies in English literature [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] . The success rate of ESR in PUI ranged from 0% to 85.7%.…”
Section: Outcome Of Different Emergency Treatmentsmentioning
confidence: 99%
“…Comparing with delayed urethroplasty, 4 our approach has several advantages as this surgical procedure is (i) effective, safe, and quick; (ii) minimally invasive, avoiding extensive operations in severely injured patients; (iii) able to have spontaneous voiding 34.5 -6.9 days (ranging from 28 to 42 days) after surgery, compared with other procedures 25 ; (iv) not required to carry the preoperative long-term urethral catheterization for the delayed surgery, which avoids patients' inconvenience and decreases the possibility of UTI or stone formation; (v) avoids tissue damage such as ED [24][25][26][27] that might be ceased by delayed surgery; (vi) suitable for treatment in smaller hospitals with lack of advanced equipment (such as flexible ureteroscope); and (vii) shorter hospital stay (8.5 days) compared with delayed surgery (35.2 days). 32,33 The success rates of endoscopic realignment range from 72% to 100%. 4,28 Three patients in this study had urinary retention, which can easily be treated with suprapubic aspiration or catheterization.…”
Section: Figmentioning
confidence: 99%